2016
DOI: 10.1002/ecs2.1210
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and controls on burned area for two contrasting fire regimes in Southern California

Abstract: An improved understanding of the mechanisms that regulate wildfire risk at local to regional scales is needed for the design of effective fire and ecosystem management. We investigated the spatial distribution of burned area in Southern California during 1960–2009 using five different data‐driven methods: multiple linear regression, generalized additive models (GAMs), GAMs with spatial autocorrelation, non‐linear multiplicative models, and random forest models. We used each method to separately develop burned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 91 publications
0
17
1
Order By: Relevance
“…Thus, post-dispersal seed predation does not predict good expectations for pine species in non-masting years. Contrary to previous studies developed in this area (see [34,38,50]), the high emergence levels of unprotected seeds indicated that seed predation was not significant in our experiment, but post-emergence seedling herbivory was a key factor.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, post-dispersal seed predation does not predict good expectations for pine species in non-masting years. Contrary to previous studies developed in this area (see [34,38,50]), the high emergence levels of unprotected seeds indicated that seed predation was not significant in our experiment, but post-emergence seedling herbivory was a key factor.…”
Section: Discussioncontrasting
confidence: 99%
“…Under ongoing global change, models fitted to simulate forest occupancy under a climate change scenario project a reduction in the P. sylvestris Spanish range and a decline in P. nigra forests, whereas P. pinaster would maintain or increase the area it occupies [35,37]. Forest fires, which are natural components of Mediterranean forest ecosystems [38] might change pine species distribution through altering post-fire initial recruitment. Fire significantly reduces seedling emergence and survival rates in the short term and seed availability is a crucial variable for post-fire natural regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In ecological applications, such as land cover classification or burned area mapping, RFs often produce more accurate and interpretable results than linear or additive models [18,36,77].…”
Section: Random Forest Algorithmmentioning
confidence: 99%
“…Globally, most fire-prone regions are characterized by a singular type of fire regime that is prescribed by dominant vegetation, climatology, and ignitions [8][9][10]. Southwestern California, by contrast, has two distinct types of wildfires that are delineated seasonally through atmospheric circulation patterns [7,11]. One fire regime is associated with Santa Ana winds that occur when a strong regional pressure gradient produces downslope offshore katabatic wind events across the southward and westward facing slopes of the peninsular and transverse ranges.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, non-Santa Ana fires predominately occur during the summer months when synoptic-scale winds are generally weak. Several recent studies have begun to demonstrate the distinctions between these two regimes, including modeling their dominant drivers and socioeconomic impacts [7,[11][12][13], but they have not yet delineated spatial extents to determine if well-defined boundaries exist between regimes.…”
Section: Introductionmentioning
confidence: 99%